BUILDING DATABASEHASIL EVALUASI BELAJAR SISWA PADA SMAN 2 KOTA TANGERANG - Padeli Padeli; Mulyati Mulyati; Alvega Awanda (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
Design of database system is a requirements that are needed in the management of student scores on SMAN 2 Tangerang to assist in the processing and storage of the archive as media student’s score the value where the value of the storage system that runs currently still usingarchive book (BIS). This causes problems such as a stacking of work load on the one hand and the long operational time when input the score. In addressing the problem then it needs a system that is able to support the process of insertion of the value that has been focused on theoperator/admin as the parties enter the value into the data of the school.So to analyze the poblems occurred then needed some research methods include methods of data colletion, observation, and a literature review. Then the data that there has been continued with the SWOT method, this method describes the shortcomings and advantages of the system, then he obtained a solution. After doing analysis, and continued with the process of designing the system.